Knowledge Of Children's Hand Washing Through Counseling During The Covid-19 Pandemic In Sukamukti Village, Garut Regency - Nizar Alam Hamdani; Irman Nurichsan; Andri Cahya Nugraha; Reo Eka July Nurholis; Fitry Yanica; Nadiyya Nur Maulidanti (Indonesian Journal of Community Empowerment (IJCE), 2022)
ABSTRACT One of the efforts to prevent the Covid-19 virus can be done by living clean habits such as getting used to washing hands with soap. This service activity provides handwashing education to early childhood in Sukamukti Village, Cilawu District, Garut Regency with the aim of providing awareness as an effort to prevent during a pandemic. Obtaining data from this study was obtained using a Quasi Experimental with one-group pre-test post-test desaign, which was filling out a questionnaire before and after counseling. Samples were taken of 30 people consisting of boys and girls with different age ranges. The results obtained showed an increase in children's knowledge about the importance of washing hands from the criteria both before counseling by 70% and after by 77%. This increase proves the hypothesis that the provision of education can increase children's awareness about clean living behavior. ABSTRAK Upaya pencegahan virus Covid-19 salah satunya dapat dilakukan dengan cara perilaku hidup bersih seperti membiasakan mencuci tangan menggunakan sabun. Kegiatan pengabdian ini melakukan pemberian edukasi mencuci tangan kepada anak usia dini di Desa Sukamukti Kecamatan Cilawu Kabupaten Garut dengan tujuan memberikan kesadaran sebagai upaya pencegahan di masa pandemi. Perolehan data dari penelitian ini didapatkan dengan menggunakan Quasi Eksperimental dengan one-group pre-test post-test desaign, yaitu dilakukannya pengisian kuesioner sebelum dan sesudah penyuluhan. Sampel yang diambil sebanyak 30 orang terdiri dari anak laki-laki dan perempuan dengan rentang usia yang berbeda. Hasil yang diperoleh memperlihatkan terjadinya peningkatan pengetahuan anak mengenai pentingnya mencuci tangan dari criteria baik sebelum penyuluhan sebesar 70% dan sesudah sebesar 77%. Adanya peningkatan ini membuktikan hipotesa bahwa pemberian edukasi dapat meningkatkan kesadaran anak mengenai perilaku hidup bersih.